Dominica : Joint Staff Assessment of the Interim Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper provides the joint assessment of the staff of the World Bank and the IMF on the interim poverty reduction strategy paper (I-PRSP) prepared by the government of the Commonwealth of Dominica and submitted to the World Bank and the IMF. The preparation of this I-PRSP-the later full PRSP-is intended to provide a framework for assistance under the poverty reduction and growth facility. The authorities have consented to the publication of both the I-PRSP and the joint staff assessment (JSA).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet